PENGARUH PANJANG STACK SELUBUNG KABEL TERHADAP PERUBAHAN SUHU PADA SISTEM PENDINGIN TERMOAKUSTIK - Indah Kharismawati; Hanif Rafika Putri (Program Studi Fisika Universitas Negeri Jakarta, 2017)
Research on environmentally friendly thermo-acoustic coolants uses a heat exchanger from the cable sheath material. The resonator tube used in the thermoelectric cooler is a 5.25 cm diameter PVC (polyvinyl chloride) tube with a length of 87 cm. Variations in stack lengths of 4cm, 5cm, 6cm, 7cm, and 8cm were performed to obtain results on thermoelectric coolers. Results are available on the use of stack length 4 cm high temperature 21.6 oC from the initial temperature), the stack length 5 cm high temperature 21.1 oC from the initial temperature (room temperature), the stack length of 6 cm resulted in a maximum temperature drop of 22.6 oC from the initial temperature (room temperature), the stack length of 7 cm resulted in a maximum temperature drop of 22.0 oC from the initial temperature (room temperature), while the stack length of 8 cm resulted in a decrease in temperature maximum of 23.3 oC from the initial temperature (room temperature). Keywords: Thermoacoustic, stack, temperature changes.